2014
DOI: 10.1017/s0954579414000492
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase Val158Met genotype moderates the effect of disorganized attachment on social development in young children

Abstract: Children with histories of disorganized attachment exhibit diverse problems, possibly because disorganization takes at least two distinctive forms as children age: controlling-punitive and controlling-caregiving. This variation in the developmental legacy of disorganization has been attributed primarily to variations in children's rearing experiences. Here an alternative explanation of these divergent sequelae of disorganization is evaluated: one focused on genotype. Structural equation modeling was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 113 publications
(167 reference statements)
1
38
0
Order By: Relevance
“…The decision to treat all Met-carriers as members of a single group was based on previous GXE studies and on association studies in which aggression was the measured outcome (Frigerio et al, 2009;Albaugh et al, 2010;Langley, Heron, O'Donovan, Owen, & Thapar, 2010;Hygen et al, 2014). Moreover, this approach is based on the premise that the effects of SLEs on aggressive behavior would not vary across heterozygote and homozygote Met-carriers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to treat all Met-carriers as members of a single group was based on previous GXE studies and on association studies in which aggression was the measured outcome (Frigerio et al, 2009;Albaugh et al, 2010;Langley, Heron, O'Donovan, Owen, & Thapar, 2010;Hygen et al, 2014). Moreover, this approach is based on the premise that the effects of SLEs on aggressive behavior would not vary across heterozygote and homozygote Met-carriers.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies indicate that low birth weight (Thapar et al, 2005) and ADHD (Caspi et al, 2008;Langley et al, 2010) increase the risk of antisocial behavior among Val homozygotes. Likewise, Perroud et al (2010) reported that Val allele carriers displayed a greater inclination toward anger when exposed to sexual abuse than did Met homozygotes, and Hygen et al (2014) found the Val/Val genotype to be associated with increasing levels of aggression in individuals with higher levels of disorganized attachment. None of these studies, however, tested whether the detected GXE effects were more or less consistent with diathesisstress or differential susceptibility models of Person ϫ Environment interaction, as was done in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, numerous reports have appeared documenting such GϫE interplay (e.g., Babineau et al, 2015;Bresin, Sima Finy, & Verona, 2013;Brown et al, 2013;Hygen et al, 2015;Hygen, Guzey, Belsky, Berg-Nielsen, & Wichstrøm, 2014); however, the GϫE field has been subjected to controversy and critique (e.g., Duncan & Keller, 2011). Nevertheless, prior research indicates that the OXTR SNP rs53576 interacts with various environmental factors in predicting diverse behavioral and psychological phenotypes.…”
Section: Gene-؋-environment Interactionmentioning
confidence: 99%
“…The Maternal Adversity, Vulnerability and Neurodevelopment Project (Canada) was sampled for 2 studies; Graffi et al, 2015;Graffi et al, 2018with data collected between 2003 and Zimmerman et al (2009) both used data collected from the Regensburg Longitudinal Study (Germany), with longitudinal data collected between 1974 and 2005. Two studies used a sample population from the Trondheim Early Secure Study (Norway): Hygen et al (2014) and Viddal et al (2017), using data collected between 2007 and 2011. The Budapest Infant Parent Study (Hungary) was used across 3 studies: Gervai et al (2005), Lakatos et al (2000), and Lakatos et al (2002).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Furthermore, given the established importance of maternal sensitivity in attachment organization, this was measured in 12 studies. A further 7 studies (Borelli et al, 2017;Humphreys et al, 2015;Hygen et al, 2014;Kochanska et al, 2009;Li et al, 2016;Viddal et al, 2017;Zimmerman et al, 2009) identified the attachment status between child and caregiver as the candidate environmental factor, observing the interplay between genetic marker and attachment to moderate externalized behaviors. Three studies (Gervai et al, 2005;Lakatos et al, 2000Lakatos et al, , 2002 included within the review did not identify environmental factors, reporting only on candidate gene associations with attachment.…”
Section: Environmental Factors Identifiedmentioning
confidence: 99%